Comunicación alternativa en la comunidad Lampata Chasqui. - Proaño Vite, Deysi Lorena (2018)
The research project was developed with the purpose of determining the importance of alternative communication in the community of Lampata Chasqui. Considering as problematic that the mentioned community does not have an active and permanent presence in the local media, so it can not promote its products, tourist places, needs, social problems, ideologies, customs and traditions, which allow them to promote their development and community progress. The methodology applied in the research was framed in the qualitative and quantitative approach, conjugated with the bibliographic design, which allows to gather the scientific and technical foundations about the variables of research and field research, which allow to collect the information of the Lampata community. Chasqui The techniques applied in the research were the survey directed to the community's inhabitants and the interview directed to a social communicator and a local media. The data provided by the research reached a social impact, because they allow determining the specific contribution of alternative communication as a strategy for community development, through the promotion and massive dissemination of the attractions and products offered by the community, as well as its cultures, traditions and parties to encourage the visit of tourists and also as a space to discuss their needs and opinions. The results obtained in the investigation show that 56% of the inhabitants consider that through the media can contribute to the development of the community, in the same way 54% indicate that the most viable alternative communication strategy would be a weekly radial program in which the needs, tourist attractions, culture and tradition of the sector can be disseminated.